Land constraints and agricultural intensification in Ethiopia: A village-level analysis of high-potential areas - Headey, Derek D.; Dereje, Mekdim; Ricker-Gilbert, Jacob; Josephson, Anna; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2013)
This paper explores the race between these two countervailing forces, with the goal of informing two important policy questions. First, how do rural Ethiopians adapt to land constraints? And second, do land constraints significantly influence welfare outcomes in rural Ethiopia? To answer these questions we use a recent household survey of high-potential areas. We first show that farm sizes are generally very small in the Ethiopian highlands and declining over time, with young rural households facing particularly severe land constraints. We then ask whether smaller and declining farm sizes are inducing agricultural intensification, and if so, how. We find strong evidence in favor of the Boserupian hypothesis that land-constrained villages typically use significantly more purchased input costs per hectare and more family labor, and achieve higher maize and teff yields and high gross income per hectare.